THE EFFECT OF RISK DISCLOSURE AND INVESTORS' ATTENTION ON IPOs INITIAL RETURN OF INDONESIAN COMPANIES - Rr. Sri Handayani; Puspita Handayani (Assets: Jurnal Akuntansi dan Pendidikan, 2022)
ABSTRACTThe research objective is to examine and analyze the effect of internal risk disclosure, external risk disclosure, investment risk disclosure, and investors' attention on initial return. This research is causality research and uses secondary data. The population is a company that conducts IPOs on the Indonesia Stock Exchange (IDX) in the 2011-2018 period with 224 companies. The sampling technique used was purposive sampling and obtained a total of 210 companies. The research results stated that there is no effect of internal risk disclosure, external risk disclosure, and investment risk disclosure on initial returns. There is a significant positive effect of investors' attention on initial returns.ABSTRAKTujuan penelitian yaitu menguji dan menganalisis pengaruh pengungkapan risiko internal, pengungkapan risiko eksternal, pengungkapan risiko investasi dan investor attention terhadap initial return. Penelitian ini merupakan penelitian kausalitas. Data yang digunakan sekunder. Populasi adalah perusahaan yang melakukan IPO di Bursa Efek Indonesia (BEI) pada periode 2011- 2018 dengan jumlah 224 perusahaan, teknik pengambilan sampel menggunakan purposive sampling dan diperoleh jumlah sampel penelitian sebanyak 210 perusahaan. Hasil penelitian antara lain, yaitu tidak terdapat pengaruh pengungkapan risiko internal, pengungkapan risiko eksternal dan pengungkapan risiko investasi terhadap initial return, terdapat pengaruh signifikan positif atensi investor terhadap initial return.